ABOUT THE METHODOLOGY OF THE LEGAL SERVICE IN THE REPUBLIC OF UZBEKISTAN - Z. K. Ayupova; D. U. Kussainov; Winston Nagan (Scientific Journal of Pedagogy and Economics, 2019)
In the entire countries of the world priority directions creation of perfect legislation, providing its steady execution, increase of legal culture of population and public servants, clear determination of rights and duties of the citizens, public and management authorities were considered. Legal service of public organs and organizations, managing subjects has an important value in this process. Legal service actively participates in the preparation of projects of normative-legal acts, in realization of the legal examination, since the process of acceptance to providing of their execution; change, stopping and execution of economic agreements; in providing legal facilities of property safety; in the observance of labor legislation and strengthening of labor discipline; in defense in courts and other organizations of rights and legal interests of corresponding organs and managing subjects. In the developed states of the world scientific researches carefully investigate the field of legal service and providing of legal help in the process of perfection of legal frameworks of the legal state and civil society. An important value has research of the concepts “Legal service” and “legal help”, perfection of bases of the legal adjusting of activity of legal service, research on the basis of new approaches of the system of legal service, legal status and basic directions of activity, participating of legal service in providing of supremacy of law and legality in activity of public organs and managing subjects, in law-making, increase of legal consciousness and legal culture of citizens.